Validation of quantitative polymerase chain reaction with Southern blot method for telomere length analysis. (18th January 2018) - Tarik, Mohamad; Ramakrishnan, Lakshmy; Sachdev, Harshpal S; Tandon, Nikhil; Roy, Ambuj; Bhargava, Santosh K; Pandey, Ravindra M
Aim: Telomere length (TL) measurement by quantitative polymerase chain reaction (PCR) has been widely accepted, but limited information regarding its validation with a gold-standard technique is available.Materials & methods: We measured TL by Southern blot and monochrome multiplex quantitative PCR (MMqPCR) and validated the results of TL in leukocytes of 94 participants with mean age 43.2 years, BMI 19–41 (mean 27.8 ± 4.3) kg/m 2 .Results: A significant positive correlation was observed between TL measured by MMqPCR and Southern blot assay (correlation coefficient r = +0.896, p < 0.0001). The inter- and intra-assay CVs of the MMqPCR assay were 5.3 and 4.07%, respectively.Conclusion: We observed that experimental discrepancies have an impact on TL analysis and there is a need to improve the optimum conditions. Lay abstract: The aim of this study was to validate the relative telomere length measurements by different methods. We measured leukocyte telomere lengths by Southern blot and monochrome multiplex quantitative polymerase chain reaction in 94 participants and a strong correlation was shown between both techniques. The results of our study suggest that the monochrome multiplex quantitative polymerase chain reaction method can be employed reliably for measurement of telomere length in epidemiological studies involving a large number of samples.